2022
DOI: 10.1007/s00394-022-03000-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of income on diet quality and daily iron and zinc intake: analysis of the National Diet and Nutrition Survey of British females aged 11–14 and 15–18 years

Abstract: Purpose A negative socio-economic gradient exists for diet and health outcomes. Since cheaper diets are associated with increased energy and lower nutrient density, we investigated the influence of income on iron and zinc intakes and overall diet quality for adolescent (DQI-A) females aged 11–18 years. Methods National Diet and Nutrition Survey (NDNS years 7 and 8) data for iron and zinc intake and overall diet quality was assessed by household income qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Income can influence the quality of a person’s diet. 28 Currently, antivascular endothelial growth-factor therapy is the primary treatment for AMD, which is expensive and requires repeated injections. 29 Furthermore, AMD patients are usually over 45, and most of them are their families’ main breadwinners.…”
Section: Resultsmentioning
confidence: 99%
“…Income can influence the quality of a person’s diet. 28 Currently, antivascular endothelial growth-factor therapy is the primary treatment for AMD, which is expensive and requires repeated injections. 29 Furthermore, AMD patients are usually over 45, and most of them are their families’ main breadwinners.…”
Section: Resultsmentioning
confidence: 99%
“…Interprofessional working is essential for patient safety and outcomes, not to mention respecting the diverse roles of individuals that make up the healthcare team (27). The need for multi-disciplinary working is crucial given the high demand for supporting more diverse patient populations, such as those within communities at high risk of poor health and social outcomes (28)(29)(30), people being discharged from hospital (31), and older people living in residential care homes (32) . When considering the needs of groups at nutrition risk, aspects of socioeconomic inequalities should include the use of food banks and how this impacts individuals living with chronic disease.…”
Section: Utilising the Knowledge And Skills Of Subject Specialistsmentioning
confidence: 99%
“…Hashimoto et al found a positive association between education and diet quality and suggested that the diet quality score of high or middle education was higher than low education for both generations ( 14 ). Another study showed that diet quality differed by income level, and individuals in the lowest income groups were at greater risk of lower overall diet quality and inadequate nutrient intake ( 15 ). A systematic review has provided evidence for the effectiveness of health promotion interventions at the workplace on physical and mental health outcomes ( 16 ).…”
Section: Introductionmentioning
confidence: 99%